Toward an Innovation Policy for Pakistan - Speakman, John; Afzal, Kiran; Yuge, Yasuhiko; Hanna, James (World Bank, Washington, DC, 2014)
This policy paper aims to assist policy makers, as they develop the Pakistan Innovation Policy, with an independent assessment of where Pakistan stands now, an international perspective on policy priorities, a review of policy options and some implementation and institutional perspectives. The paper begins with a review of the key lessons of international experience together with a study of key international benchmarks. It takes a look at the ecosystem approach which maps the effectiveness of all the various players in innovation and also reviews progress against 12 triple helix critical success factors. The possible policy options are then enumerated and evaluated for relevance. Finally, some perspectives are provided on how to move the innovation agenda forward.